{2-[(1H-Indol-3-ylmethylidene)amino]-4,5,6,7-tetrahydrobenzo[b]thiophen-3-yl}(phenyl)methanone - Manpreet Kaur; Jerry P. Jasinski; Thammarse S. Yamuna; H. S. Yathirajan; K. Byrappa (Acta Crystallographica Section E, 2014)
The title compound, C24H20N2OS, crystallizes with two independent molecules (A and B) in the asymmetric unit, in each of which the cyclohexene rings adopt half-chair conformations. The mean plane of the indole ring is twisted from those of the phenyl and thiophene rings by 69.0 (7) and 8.3 (5)°, respectively, in molecule A and by 65.4 (9) and 6.7 (5)°, respectively, in molecule B. The dihedral angles between the mean planes of the phenyl and thiophene rings are 63.0 (4) and 58.8 (9)° in molecules A and B, respectively. In the crystal, N—H...O hydrogen bonds lead to the formation of an infinite chain along [101]. In addition, π–π stacking interactions are observed involving the thiophene and pyrrole rings of the two molecules, with a shortest intercentroid distance of 3.468 (2) Å.